Economic and operational burden associated with malnutrition in chronic obstructive pulmonary disease. Issue 4 (August 2017) - Hoong, Jian Ming; Ferguson, Maree; Hukins, Craig; Collins, Peter F.
Summary: Background: Malnutrition is common in patients with chronic obstructive pulmonary disease (COPD). This study aimed to explore its association with all-cause mortality, emergency hospitalisation and subsequently healthcare costs. Methods: A prospective cohort observational pilot study was carried out in outpatients with COPD that attended routine respiratory clinics at a large tertiary Australian hospital during 2011. Electronic hospital records and hospital coding was used to determine nutritional status and whether a patient was coded as nourished or malnourished and information on healthcare use and 1-year mortality was recorded. Results: Eight hundred and thirty four patients with COPD attended clinics during 2011, of those 286 went on to be hospitalised during the 12 month follow-up period. Malnourished patients had a significantly higher 1-year mortality (27.7% vs. 12.1%; p = 0.001) and were hospitalised more frequently (1.11 SD 1.24 vs. 1.51 SD 1.43; p = 0.051). Only malnutrition (OR 0.36 95% CI 0.14–0.91; p = 0.032) and emergency hospitalisation rate (OR 1.58 95% CI 1.2–2.1; p = 0.001) were independently associated with 1-year mortality. Length of hospital stay was almost twice the duration in those coded for malnutrition (11.57 SD 10.93 days vs. 6.67 SD 10.2 days; p = 0.003) and at almost double the cost (AUD 23, 652 SD 26, 472 vs. 12, 362 SD 21, 865; p = 0.002) than those who were well-nourished. Conclusion: Malnutrition is an independent predictor of 1-year mortality and healthcare use in patients with COPD. Malnourished patients with COPD present both an economic and operational burden.